Rigid bicyclo[3.3.0]octane (octahydropentalene): a heavily constrained novel aliphatic template for molecular self-assembly - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This Letter reports the utility of a heavily constrained cis-fused bicyclo[3.3.0]octane (octahydropentalene) aliphatic template for effecting molecular self-assembly. An attractive feature of this system is its heavily constrained alicyclic backbone that would allow for the exploration of self-assembling systems with conformationally ordered features. (C) 2008 Elsevier Ltd. All rights reserved.

Rhenium(I) tricarbonyl complex of 5,20-bis(p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin: first X-ray structural characterization of metal complex of 21-selenaporphyrin - Ghosh, Avijit; Gonnade, Rajesh G.; Ravikanth, Mangalampalli (Dalton Transactions, 2013)
Synthesis and first structural characterization of hexa coordinated rhenium(I)tricarbonyl complex of 5,20-bis( p-tolyl)-10,15-bis(p-methoxyphenyl)-21-selenaporphyrin 3 are described. The Re(I)complex of 21-selenaporphyrin 3 was synthesized by treating free base 21-selenaporphyrin in 1,2-dichlorobenzene with Re(CO)(5)Cl at reflux for 7 h and analyzed using mass, NMR, FT-IR, UV-vis and electrochemical techniques. The first structure of metal complex of 21-selenaporphyrin was determined by X-ray single crystal analysis. The crystal structure revealed that the Re(CO)(3) coordinates to two of the three inner nitrogens and one selenium to produce compound 3. The selenophene ring bent towards the Re(I)ion and the selenium is displaced by 0.41 angstrom from the mean plane of 24-atoms to coordinate with Re(I)ion in eta(1)-fashion. The 21-selenaporphyrin is distorted in compound 3 compared to free base 21-selenaporphyrin. H-1 and C-13 NMR studies indicated that compound 3 exhibits fluxional behaviour in coordination mode of binding in solution. The compound 3 is highly stable and does not undergo decomplexation under acidic conditions. The absorption spectra showed three broad Q-bands and splitted Soret band and electrochemical studies indicated that compound 3 is stable under redox conditions.

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions

Reactivities of silaimines with boranes: from cooperative B-H bond activation to donor stabilized silyl cation - Bisai, Milan Kumar; Sharma, Vishal; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
The recently published silylene with a tris(trimethylsilyl) group, PhC(NtBu)(2)SiSi(SiMe3)(3) (1), was reacted with the organic azides such as SiMe3N3 and AdN(3) to form the respective hypersilylsilaimines, PhC(NtBu)(2)Si(=NR)Si(SiMe3)(3) 2 (R = SiMe3) and 3 (R = Ad). The B-H bond of HBpin or HBcat was split across the Si=N bond upon reaction with 2, which generated 4 and 5, respectively. However, we could not obtain the crystals of 4 and 5 appropriate for X-ray diffraction. Subsequently, we performed the analogous reactions with a related silaimine PhC(NtBu)(2)Si(=NSiMe3)N(SiMe3) 2 (2') and isolated similar B-H bond activated products 6 and 7. The reaction of 2' with HBCl2 resulted in donor stabilized silyl cations (8 and 9) supported by an amidinate ligand.

Rapid synthesis of the epi-biotin sulfone via tandem S,N-carbonyl migration/aza-michael/spirocyclization and haller-bauer reaction - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (ACS Omega, 2022)
A synthesis of 2-epi-biotin sulfone was accomplished from commercially available L-cysteine. The synthesis features an unprecedented tandem S,N-carbonyl migration/aza-Michael/spirocyclization reaction from an L-cysteine-derived enone with aq. ammonia, in which three new sigma bonds and two rings are formed. In addition, the synthesis includes a highly diastereoselective late-stage Haller-Bauer reaction of sulfone for direct introduction of the carbon side chain.

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Room temperature Z-selective hydrogenation of alkynes by hemilabile and non-innocent (NNN)Co(ii) catalysts - Sharma, Dipesh M.; Gouda, Chandrakant; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2022)
Hemilabile and phosphine-free quinolinyl-based NNN-type pincer and non-pincer cobalt complexes were developed for the room temperature catalytic transfer semi-hydrogenation of alkynes to Z-alkenes. Treatment of the quinolinyl-amine ligand, [C9H6N(NH)CH2CH2NEt2] ((NNN2NEt2)-N-Q-N-CH)-H with CoX2 afforded the pincer complexes kappa(3)-((NNN2NEt2)-N-Q-N-CH)CoX2 (X = Cl, Br), whereas, the quinolinyl-amide ligand, [C9H6N(NH)C(O)CH2NEt2] ((NNNNEt2)-N-Q-N-C(O))-H gave chelate anionic complexes kappa(2)-((NN)-N-Q)CoX2((NHNEt2)-H-C(O)) (X = Cl, Br). The well-defined anionic non-pincer cobalt complexes efficiently catalyzed the semi-hydrogenation of diverse alkynes to deliver highly chemoselective and stereodivergent Z-alkenes at room temperature. This hydrogenation exhibited broad substrate scope with the tolerance of sensitive functional groups, such as -Cl, -Br, -I, -OH, -NH2, -COOMe, and pyridinyl, employing a stable and user-friendly ammonia borane hydrogen source.

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).

Regio- and stereoselective construction of 1,3,5-triaroylcyclohexanes via KO t Bu-mediated cyclotrimerization of aryl vinyl ketones - Mahale, Sachin D.; Yadav, Vinita; Gonnade, Rajesh G.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2024)
Herein, we disclose a simple one-pot method for an efficient regio- and stereoselective synthesis of 1,3,5-triaroylcyclohexanes from aryl vinyl ketones using potassium tert-butoxide. The developed protocol allows the construction of various symmetrically substituted cyclohexanes in good to excellent yields. The major product 2 also can be converted to the product 3 (all equatorial) conveniently by acid catalysis. This protocol features a good substrate scope and functional group compatibility.

Regulating the polyethylene microstructure by increasing steric crowding in naphthoxy imine-ligated Ni(II) complexes - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Polymer Chemistry, 2024)
Ligands play a prominent role in ethylene polymerization. However, it is a highly challenging task to regulate branching through ligand modifications. Here we report the synthesis of systematically sterically tailored naphthoxy imine-ligated nickel complexes (Ni1, Ni2, and Ni3), their performance in ethylene polymerization, and how the ligand steric controls branching in the resultant PE. Ni1-Ni3 were prepared in one step with an excellent yield (73-93%). The identity of these complexes was unambiguously ascertained using H-1, C-13, 2D NMR spectroscopy, mass analysis, and single-crystal X-ray diffraction. The molecular structure revealed a cis arrangement of alkyl/aryl and donor groups (C-Ni-D), which is necessary for initiating ethylene polymerization. Buried volume contours suggested Ni3 to be sterically the most bulky among the three. When exposed to ethylene, the three nickel complexes Ni1, Ni2, and Ni3 produced polyethylene with excellent activity. As predicted by buried volume calculations, dibenzhydryl-substituted Ni3 outperformed sterically less crowded Ni1 and Ni2. Careful analysis of the resultant PE disclosed that sterically less encumbered Ni1 and Ni2 produce PE with high branching (43-54 branches/1000-C atoms) density. However, the bulkiest Ni3 revealed much lower branching (28 branches/1000-C atoms) and a high TOF of 35 400 mol of PE per mol of Ni per h, along with a high molecular weight of PE (61 000 Da). The steric bulk in Ni3, most likely, reduces chain-walking and thus lowers branching in the resultant PE. As compared to the literature-reported analogous Pd1 catalyst, the Ni3 catalyst discloses high TOF, high molecular weight, and less branched, linear polyethylene.
Keywords: Catalyzed Olefin Polymerization; High-Temperature; Molecular Weight